Personal centered care in long term residences: how to evaluate client satisfaction? - Pereira, Fernando A. (2020)
The evaluation of client’s satisfaction allows improving the quality of services as a result of feedback from their clients. The purpose of this study is to develop a scale to assess the client s satisfaction under the scope of personal-centered care model (PCC). A cross-sectional study, based on personal interviews by using a client’s satisfaction questionnaire, was conducted among 160 older adults from 12 long-term care services (LTC). Principal component analysis was performed to assess the underlying scale structure and factor loadings were computed. We excluded questions on issues that are not easily assessed by the elderly and we reworded others items to make them clear and simple questions for comprehension among elderly and unambiguous in regards the theoretical construct. We proposed a more succinct instrument, sensitive to the personal-centered care issues, to assessing the client’s satisfaction of the LTC.